Multi-scale approach to analyse the evolution of soft rock coastal cliffs and role of controlling factors: a case study in South-Eastern Italy. Issue 1 (1st January 2021) - Lollino, Piernicola; Pagliarulo, Rossella; Trizzino, Rosamaria; Santaloia, Francesca; Pisano, Luca; Zumpano, Veronica; Perrotti, Michele; Fazio, Nunzio Luciano
Abstract: The evolution of soft rock coastlines is strictly related to natural and anthropogenic conditions, which in some cases can determine also an acceleration of coastal retreat. The recent evolution of a soft rocky coastal stretch on the Italian southern Adriatic sector is analysed. To investigate the most important contributing factors to coastal evolution, a detailed multi-temporal (1954–2017) morphological analysis with photo-interpretation is carried out, which allows gaining a general understanding of the cliff evolution. The coastal retreat was then evaluated by exploiting the Digital Shoreline Analysis System (DSAS) tool. From that, site-specific analyses are carried out to explore the role of four environmental factors: rock mechanical properties, geostructural setup of the rock mass along the coast, emerged rock platform at the toe, and the storm waves. Analyses highlighted how the most significant retreat is detected along cliff segments characterized by the presence of low strength rocks susceptible to water-induced weakening, moderate fracturing degree of the rock mass, absence of the emerged platform at the toe, and wave storms. This work shows how a multi-scale methodology could represent an efficient approach to gain an interpretation of the instability processes and thus prepare risk mitigation plans and land management strategies.